Kim byli zmarli z cmentarza zanikłej wsi Gać? Dane historyczne „kontra” datowanie bezwzględne - Gembicki, Maciej; Krzepkowski, Marcin; Polcyn, Marek; Lynch, Paige (Folia Praehistorica Posnaniensia, 2025)
The cemetery of the abandoned village of Gać, located in Greater Poland, offers new insights into its chronology and function. Excavations conducted since 2017 have uncovered 180 burials, exhibiting stratigraphic complexity and a changing spatial organization. Based on 30 radiocarbon dates, Bayesian chronological modeling revealed that the cemetery was in use from the mid-17th to the end of the 18th century, much later than previously assumed. The results challenge earlier interpretations of the site as a 14th-century parish cemetery. Instead, the cemetery appears to have emerged after the decline of the village parish and may have served specific purposes, such as a cemetery for Protestant communities. By combining radiocarbon dating, stratigraphy, and Bayesian modeling, the study provides a refined chronology and highlights the cemetery’s role during the village’s decline. These findings contribute to understanding post-medieval burial practices and underscore the importance of multi-method approaches in reconstructing complex archaeological sequences.